The Government's Response to the Online Transportation Sub-Sector Economic Resilience in Anticipating the Covid-19 Impact: A Literature Review - Nicholas Aryo Bimo Wuryanto; Erfianti Erfianti; Dyah - Mutiarin (Institut Pemerintahan Dalam Negeri, 2021)
The Covid-19 pandemic has significantly affected human life, especially in the Indonesian economy and the transportation sub-sector. This research explains the Government's response in economic resilience and online transportation in anticipating the pandemic’s impact. Secondary data were analyzed using the descriptive qualitative method. The results showed that various initial responses were used to overcome the pandemic in online transportation, such as tight health protocols in customer facilities. These include purchasing PPE, medical devices, hospital upgrades, intensive doctors, and support for medical personnel by the government. Furthermore, there is an effort to strengthen economic resilience, especially for workers in the online transportation sub-sector. Keywords: The Impact of Covid-19; Economic Resilience; Government Response, Online Transportation; Resilience Response